Efeitos de parâmetros de fermentação na produção de etanol a partir de resíduo líquido da industrialização da mandioca (manipueira) - Suman, Priscila Aparecida [UNESP]; Urbano, Luiz Henrique [UNESP]; Leonel, Magali [UNESP]; Mischan, Martha Maria [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2011)
Effect of fermentation parameters on ethanol production from cassava liquid residue (manipueira). "Manipueira", a liquid residue from the processing of cassava starch and flour, has recognized high pollution potential. Aiming at a possible use of "manipueira" as raw material for ethanol production, this study aimed to evaluate the effect of the percentage of inoculated yeast and fermentation temperature on the chromatographic profile of the components of wine of "manipueira". The residue was characterized for starch and sugar content, as well as pH and total acidity. The residue was hydrolyzed by the action of enzymes Termamyl 120 L and AMG 300 L. The hydrolysate obtained was fermented under different experimental conditions. A factorial central composite design (2(2)) with two independent variables and the response surface methodology were used to evaluate the results. The results showed a significant effect of variable parameters on the components of wine. The conditions of low fermentation temperature and lower percentages of inoculated yeast were the most appropriate to obtain ethanol from "manipueira".
Effect of fermentation parameters on ethanol production from cassava liquid residue (manipueira)
Keywords: cassava; residue; ethanol; chromatography